Combined endoscopic and mini-open repair of chronic complete proximal hamstring tendon avulsion: a novel approach and short-term outcomes. Issue 4 (31st May 2021) - Factor, Shai; Khoury, Amal; Atzmon, Ran; Vidra, Matias; Amar, Eyal; Rath, Ehud
Abstract: To evaluate the outcome of a novel, combined endoscopic and mini-open repair (CEMR) of a chronic complete retracted proximal hamstring tendon avulsion (PHA). A retrospective case series of a single-surgeon database for all patients, with a minimum of 1-year follow-up, who underwent CEMR between July 2015 and September 2019 was performed. Patients were evaluated for their functional outcome using the Perth Hamstring Assessment Tool (PHAT). At the latest follow-up, patients were evaluated for their muscle strength, subjective satisfaction and post-operative complications. Twelve patients who underwent endoscopic surgery for chronic PHA were identified, of which seven patients underwent CEMR. After exclusion of one patient from the study due to an open claim for health insurance, six patients (five males) with a mean age of 48 years (range 20–61 years) were evaluated. The mean time from injury to surgery was 12 months (range 2–43 months). At a mean follow-up of 28 months (range 12–55 months), the average PHAT score was 73 (range 70–80). The mean subjective activity level percentage improved from 34 (range 20–50) pre-surgery to 81 (range 75–90) post-surgery. The mean strength of the quadriceps, hamstring at 30°, and hamstring at 90° of the operated leg compared to the uninjured leg did not differ significantly. One patient underwent adhesiolysis 1 year after the index procedure for treatment of subcutaneous adhesions. CEMR is a viable and safe option for the treatment of chronic complete proximal hamstring tears, with good to excellent short-term functional outcome. Level of evidence: IV.